2016
DOI: 10.1161/circresaha.116.306923
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Mechanisms of Cardiovascular Disorders in Diabetes

Abstract: The clinical correlations linking diabetes with accelerated atherosclerosis, cardiomyopathy, and increased post-MI fatality rates are increasingly understood in mechanistic terms. The multiple mechanisms discussed in this review seem to share a common element: prolonged increases in ROS production in diabetic cardiovascular cells. Intracellular hyperglycemia causes excessive ROS production. This activates nuclear poly(ADP ribose) polymerase (PARP), which inhibits GAPDH, shunting early glycolytic intermediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
361
1
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(391 citation statements)
references
References 182 publications
(222 reference statements)
9
361
1
20
Order By: Relevance
“…But the roles of miRNAs in diabetes and its cardiovascular complications are not fully discovered [1820]. It was reported that miR-195 increased ROS production via Sirt1 and Bcl-2, and inhibition of miR-195 may be a promising therapeutic strategy for lipotoxic cardiomyopathy [21].…”
Section: Introductionmentioning
confidence: 99%
“…But the roles of miRNAs in diabetes and its cardiovascular complications are not fully discovered [1820]. It was reported that miR-195 increased ROS production via Sirt1 and Bcl-2, and inhibition of miR-195 may be a promising therapeutic strategy for lipotoxic cardiomyopathy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Since hyperinsulinemia is associated with increased cardiovascular risk, hyperinsulinemia and hepatic portal hypoinsulinemia due to injection of insulin preparations widely used in the treatment of type 1 diabetic patients could be responsible, at least in part, for cardiovascular consequences of the disease. The results of epidemiological studies and experimental studies in animal models supported systemic hyperinsulinemia as a major plausible factor in the development of atherosclerosis in diabetic patients [6][7][8][9][10] . Insulin resistance is strongly associated with hyperinsulinemia, and is considered as the major pathologic mechanism for susceptibility to premature atherosclerosis and cardiovascular disease [11,12] .…”
Section: Introductionmentioning
confidence: 87%
“…Elevated ERS response in maternal mice with type 2 diabetes mellitus (T2DM) triggers postnatal congenial heart failure (CHD) by inducing ERS, which is evidenced by elevated CHOP, BiP, and XBP1 levels. This indicates that proper hypoglycemic management of pregnant women could reduce the prevalence of cardiovascular risk for the fetus, partially due to suppressed ERS under normal blood glucose conditions (Shah et al, 2016;Wu et al, 2016).…”
Section: ! 19mentioning
confidence: 99%